Resilience Improves the Sleep Quality in Disabled Elders: The Role of Perceived Stress - Cai, Yumei; Wang, Junlei; Hou, Liwen (Frontiers in Psychology, 2021)
The current research aims to prove the impact of resilience on sleep quality, and to investigate the mediating function of perceived stress in the paths from resilience to sleep quality among the Chinese disabled elders. Participants contained 196 disabled elders resided in the nursing houses in Shanghai. Results showed all the characteristic factors were significantly related to perceived stress and PSQI scores. High levels of resilience could significantly enhance the quality of sleep in Chinese disabled elders. In addition, the two-step mediation models also confirmed the impact of resilience on sleep quality was mediated through perceived stress in this special aged population. A better knowledge to the mechanisms of sleep quality among older adults could benefit the prevention and treatment of some geriatric diseases.